The Correlation Between Students’ Creativity And Their Writing Skill At Ma Nw Peseng - Agus Salim; Tawali Tawali; Sudirman Sudirman; Wari’ah Wari’ah (JUPE : Jurnal Pendidikan Mandala, 2020)
This research was aimed to find out the correlation between students’ creativity and their writing skill. The kind of this research was simple correlational study (quantitative approach). The population of this research was 77 of the second grade students of MA NW Peseng. The sample of this research was 21 consist of one class. The sample technique that used in this research was cluster random sampling technique by using lottery. The intruments that was used in this research were tests, that were verbal creativity test and writing test. Then the technique that used in analyzing the data was Pearson Product Moment formula. From the research, the r of xy score was higher than r-table (0.829>0.456) in 5% and 1% level of significance. Based on the result of this research, it could be concluded that there was a significant correlation between students’ creativity and their writing skill meant Alternative Hypothesis (Ha) was accepted and Null hypothesis (H0) was rejected.